Biconvex arthroplasty for treatment of the ankylosis of the temporo mandibular articulation - Edela Puricelli (Revista da Faculdade de Odontologia de Porto Alegre)
The author introduces a new technique for the surgical treatment of the ATM ankylosis.It is about and arthroplasty interposition of alloplastic material- self-polymerizing methyl methacrylate.The functional reconstruction of the ATM occurs through the construction of two spheres: one posterosuperior, fixed on the roof of the articular cavity and another one, anteroinferior, in the condylar region on the mandibula.The power vector, deviated to the skull base,and the smaller rolling friction allows correction of the mandibular latero deviation and wide mobility of the articulation.